Why Primary Rhinoplasty Fails. (29th November 2021) - Rohrich, Rod J.; Savetsky, Ira L.; Avashia, Yash J.
Abstract : Summary: Rhinoplasty remains one of the most challenging operations performed by plastic surgeons. The complexity lies in the ability to have a consistent and predictable aesthetic result. The unpredictability is mainly attributable to the interplay of manipulated internal structures and wound healing dynamics. In addition, setting realistic expectations with the patient is essential for achieving high postoperative patient satisfaction. An open rhinoplasty approach enables an accurate and in-depth evaluation and intervention. The authors provide a detailed analysis and discussion on why primary rhinoplasty fails, along with the surgical approach for preventing these failures.